A Critical Study of English Language Teaching in India: Exploring the state and trends of English language teaching in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper deals with the state of English language teaching in India at the present time. This study examines the history of English teaching in the past and present. Unlike the teaching of the vernacular language, ELT deserves more realistic approach, since it is a foreign language. This article illustrates the importance of using English as an instrument to satisfy the ever-increasing demands. As the world rises in business revolution, it has become unavoidable to keep up with that in the English medium. Therefore, a critical analysis of ELT in India would not only investigate the trend but also the suitability of the types. The way by which the learners will bring their knowledge into actual everyday practise is to satisfy their real-world needs and acquire language expertise.